An in vivo implantation study in New Zealand white rabbits for granular hydroxyapatite - Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Aziz, Mohd Yusof; Mohamed Amin, Mohamed Azril; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Zakaria@Mohamad, Zamzuri; Fazan, Fazilah (AO Research Institute Davos, 2008)
We developed hydroxyapatite (HA) granules made from local raw materials (GranuMaS™), which have been fabricated using a novel method (Patent (Pending) No. PI 2004 0748). GranuMaS™ have been fully characterized using X-ray diffraction, scanning electron microscopy, energy dispersive x-ray, Fourier transform infra-red spectroscopy and inductively coupled plasma methods. It has also been shown to comply with the ASTM F1185 - 88 (1993) specification standards. Biocompatibility studies have been performed on the product, which include neutral red cytotoxicity assay using cultured fibroblast and CRL-1427 osteoblast cells; MTT (Tetrazolium Salt) assay; cytotoxicity studies for apoptosis using Acridine Orange / Propidium Iodide (AO/PI) dual staining of V79 cells in DMEM; and COMET assay genotoxicity studies using L-929 (normal mouse epithelial) cells. An in vivo implantation study involving New Zealand White rabbits were carried out in the course of this study.